WALLABY pre-pilot survey: two dark clouds in the vicinity of NGC 1395. Issue 2 (10th August 2021) - Wong, O I; Stevens, A R H; For, B-Q; Westmeier, T; Dixon, M; Oh, S-H; Józsa, G I G; Reynolds, T N; Lee-Waddell, K; Román, J; Verdes-Montenegro, L; Courtois, H M; et al.
ABSTRACT: We present the Australian Square Kilometre Array Pathfinder (ASKAP) WALLABY pre-pilot observations of two 'dark' H i sources (with H i masses of a few times 10 8  $\rm {M}_\odot$ and no known stellar counterpart) that reside within 363 kpc of NGC 1395, the most massive early-type galaxy in the Eridanus group of galaxies. We investigate whether these 'dark' H i sources have resulted from past tidal interactions or whether they are an extreme class of low surface brightness galaxies. Our results suggest that both scenarios are possible, and not mutually exclusive. The two 'dark' H i sources are compact, reside in relative isolation, and are more than 159 kpc away from their nearest H i -rich galaxy neighbour. Regardless of origin, the H i sizes and masses of both 'dark' H i sources are consistent with the H i size–mass relationship that is found in nearby low-mass galaxies, supporting the possibility that these H i sources are an extreme class of low surface brightness galaxies. We identified three analogues of candidate primordial 'dark' H i galaxies within the TNG100 cosmological, hydrodynamic simulation. All three model analogues are dark matter dominated, have assembled most of their mass 12–13 Gyr ago, and have not experienced much evolution until cluster infall 1–2 Gyr ago. Our WALLABY pre-pilot science results suggest that the upcoming large-area H i surveys will have a significant impact on our understanding of low surface brightness galaxies and the physical processes that shape them.